The A to Z of Jainism (Scarecrow Press, 2009)
Jain is the term used for a person who has faith in the teachings of the Jinas ('Spiritual Victors'). Jinas are human beings who have overcome all passions (kasayas) and have attained enlightenment or omniscience (kevala-jnana), who teach the truths they realized to others, and who attain liberation (moksa) from the cycle of rebirth (samsara). At the core of these teachings is nonviolence (ahimsa), which has remained the guiding principle of Jain ethics and practices to this day. In comparison with other religious traditions of South Asia, Jains are few in number, comprising less than one percent of India's population. The lay and mendicant communities of the Jain, however, have maintained an unbroken presence in India for more than 2,500 years and have influenced its culture throughout this time. The A to Z of Jainism covers the history of Jainism that spans a period of more than 2,500 years. The history, values, concepts, and scriptures; eminent mendicant, lay leaders, and scholars; and places, institutions, social, and cultural factors are covered in over 450 dictionary entries. This comprehensive reference work also includes an introductory essay, explanation of the Jain scriptures, chronology, appendixes, and bibliography. This book provides an excellent introduction and overview to Jainism for scholars, students, and general readers.
Keywords: Jainism -- History -- Dictionaries; Jainism; RELIGION / Comparative Religion; Electronic books; Dictionaries; History